The Real Experience of Lay Responders Performing Cardiopulmonary Resuscitation: A Synthesis of Qualitative Evidence - Na Li; Chen Shen; Xin Yang; Rao Wang; Lian Qi Gu; Wei Zhao; Zhi Ping Chu (Frontiers Media S.A., 2024)
ObjectivesTo synthesize qualitative evidence on the experience of lay responders performing cardiopulmonary resuscitation (CPR).MethodsQualitative evidence synthesis was performed using the Thomas and Harden method. The PubMed, Cochrane Library, Web of Science, OVID Medline, Embase, CINAHL, CNKI, and WanFang databases were systematically searched. The quality of the research was assessed by the Critical Assessment Skills Program Tool (CASP).ResultsA total of 5,610 studies were identified, and 9 studies were included in the analysis. Four analytical themes were generated: emotional ambivalence before CPR, psychological tolerance during CPR, perceived experience after CPR, and enhancing psychological resilience.ConclusionLay responders face complicated psychological experience during CPR, which may be susceptible to psychological effects such as "loss aversion," "bystander effects" and "knowledge curse." In addition to the timely retraining of CPR, lay responders should be instructed to manage psychological distress and improve psychological resilience. More importantly, the psychological sequelae may be long-lasting, requiring ongoing psychological intervention and follow-up based on valuing transdisciplinarity across endeavours.